Consumer preferences and quality of services in the field of physical culture and sports - Gorskaya I.Yu.; Kravchuk T.A.; Kravchuk A.I.; Belyakova A.S. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to analyze consumer opinions on issues of interests and motivation for physical сulture and sports, the quality of physical education and health services in the Russian Federation. Methods and structure of the study. The materials of the scientific work were received at the Siberian State University of Physical Education and Sports in the process of fulfilling a state assignment on the topic “Development of a standard model for the provision of physical education and health services by non-governmental organizations, including the procedure for monitoring their quality and methodological recommendations for their implementation” (2023). Methods: theoretical analysis and synthesis of data from scientific and methodological literature, questionnaires, comparison, generalization, structuring, analysis and synthesis. The survey was conducted using Google forms (using a developed questionnaire of 20 questions) during 2023 with the participation of 5,550 people of different ages living in different regions of the Russian Federation. Results and conclusions. The analysis made it possible to identify the preferences of different age groups of the population when choosing the type, form, place for physical сulture and sports at the present stage. The most popular types of physical activity were identified (exercises in the gym, fitness club and swimming pool, playing team sports, running and Nordic walking, winter sports). Problematic aspects have been identified that limit the involvement of people in regular physical сulture and sports, including reduced motivation to exercise, an insufficient number of sports facilities in the immediate vicinity of their place of residence or work, and the rather high cost of classes for a certain part of people.